Biomechanical observations in hammer throwing: distinguishing the static and the dynamic - Maheras, A. V. (Techniques Magazine, 2018)
The complex special structure of the hammer throw, and the relatively long time that is used to obtain the final speed of the hammer, make it possible that small changes can be the causes of the differences in the distance thrown. Those differences range between fifteen and twenty meters, that is, between the world elite and mediocre throwers. This narrative will focus of certain biomechanical observations of the event that can be considered central during its execution.